Emotional : how feelings shape our thinking - Mlodinow, Leonard, 1954- (New York : Pantheon Books, 2022)
"For millennia, we have viewed thinking and feeling as fundamentally opposed processes, but extraordinary advances in psychology and neuroscience, including neuroimaging and other related technologies, have cast doubt upon this traditional conception and led to a revolution in the science of emotions."--
Includes bibliographical references (pages 209-230) and index.
Keywords: Emotions; Reason